Clinical dynamics of chronic nephritic syndrome in children - Bazarova Nigina Sobirjonovna; Tuychieva Sabohat Kurakbaevna (Genius Journals, 2023)
The study of the prevalence and clinical variability of the course of CNS, the rate of progression adapted to the indicator of a decrease in the glomerular filtration rate, the influence of risk factors and immunosuppressive therapy on the long-term prognosis of the disease remains the subject of scientific discussions, creates prerequisites for further study of this problem and determines its relevance.
Keywords: chronic nephritic syndrome; glomerulonephritis; prognosis